OxyR2 Modulates OxyR1 Activity and Vibrio cholerae Oxidative Stress Response - Wang, Hui (Infect Immun, 2017)
Bacteria have developed capacities to deal with different stresses and adapt to different environmental niches. The human pathogen Vibrio cholerae, the causative agent of the severe diarrheal disease cholera, utilizes the transcriptional regulator OxyR to activate genes related to oxidative stress resistance, including peroxiredoxin PrxA, in response to hydrogen peroxide. In this study, we identified another OxyR homolog in V. cholerae, which we named OxyR2, and we renamed the previous OxyR OxyR1. We found that OxyR2 is required to activate its divergently transcribed gene ahpC, encoding an alkylhydroperoxide reductase, independently of H(2)O(2). A conserved cysteine residue in OxyR2 is critical for this function. Mutation of either oxyR2 or ahpC rendered V. cholerae more resistant to H(2)O(2). RNA sequencing analyses indicated that OxyR1-activated oxidative stress-resistant genes were highly expressed in oxyR2 mutants even in the absence of H(2)O(2). Further genetic analyses suggest that OxyR2-activated AhpC modulates OxyR1 activity by maintaining low intracellular concentrations of H(2)O(2). Furthermore, we showed that ΔoxyR2 and ΔahpC mutants were less fit when anaerobically grown bacteria were exposed to low levels of H(2)O(2) or incubated in seawater. These results suggest that OxyR2 and AhpC play important roles in the V. cholerae oxidative stress response.